FRI0494 Secukinumab provides rapid and sustained pain relief in psoriatic arthritis: 2-year results from the future 2 study. (15th June 2017) - McInnes, IB; Mease, PJ; Schett, G; Kirkham, B; Strand, V; Williams, N; Fox, T; Pricop, L; Jugl, S; Gandhi, KK; ,
Abstract : Background: Pain remains a major clinical challenge in the treatment of psoriatic arthritis (PsA). Secukinumab (SEC) has demonstrated significant efficacy in PsA patients (pts), across a range of quality of life related outcome measures. 1, 2 Objectives: This post-hoc analysis evaluated change in pain scores from baseline (BL) to Week (Wk) 104 in PsA pts receiving SEC in the FUTURE 2 study. Methods: FUTURE 2 study design has been reported. 2 Mean change from BL in pain VAS and SF-36 bodily pain domain scores were evaluated using mixed-effect model for repeated measures (MMRM) through Wk 16 and as observed through Wk 104. Proportion of pts reporting improvements ≥clinically meaningful differences in pain VAS (mean change from BL ≥20%) was assessed. Results are reported for SEC 300 and 150mg in overall population and stratified by prior use of TNF inhibitor (TNFi; TNFi-naïve vs. inadequate responder/intolerant [TNFi-IR]). EQ–5D-3L pain item scores (no-, moderate- or extreme-pain/discomfort) were assessed as proportions. Results: Mean changes from BL in pain VAS were greater with SEC vs. placebo (PBO) by Wk 3 (least squares mean [LSM]: -16.9, -12.6 with SEC 300 and 150mg, respectively vs. -5.75 with PBO; P <0.05), and Wk 16 (LSM: -24.0 and -23.0 for SEC 300 and 150mg, respectively vs. -8.41 with PBO; P <0.05). Mean changes were sustained through Wk 104 (-26.1 and -25.9 with SEC 300 and 150mg, respectively). In both SEC groups, >50% pts reported improvements of ≥20% by Wk 3 and this increased through Wk 104. Similarly, SF-36 bodily pain domain scores improved from BL by Wk 4 and 16 with SEC vs. PBO, exceeding minimum clinically important differences of 5.0 (Wk 4: LSM: 16.2 and 16.3 for SEC 300 and 150mg, respectively vs. 5.9 with PBO; P <0.05 and Wk 16: LSM: 21.1 and 22.0 for SEC 300 and 150mg, respectively vs. 6.9 with PBO; P <0.05). Improvements in pain were consistent in TNFi-naïve and TNFi-IR pts; and of greater magnitude in the naïve subgroup (table). Based on the EQ–5D-3L pain/discomfort item, 99% pts reported moderate to extreme pain or discomfort at BL. At Wk 4, the proportion of pts with no pain or discomfort was greater for the SEC 300mg (15%) and 150mg (10%) vs. PBO (5%) and increased through Wk 104 to 28% and 16% with SEC 300 and 150mg, respectively. Conclusions: SEC provides rapid and sustained pain relief through 104 wks in pts with PsA as assessed by multiple clinically relevant patient-reported measures of pain. Improvements were reported by pts regardless of their prior TNFi therapy status. References: Strand V, et al. Ann Rheum Dis 2017;76:203–7. McInnes IB, et al. Lancet 2015;386:1137–46. Disclosure of Interest: I. McInnes Grant/research support from: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer and UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer and UCB, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer and UCB, P. Mease Grant/research support from: Abbvie, Amgen, BMS, Celgene, Crescendo Bioscience, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, and UCB, Consultant for: Abbvie, Amgen, BMS, Celgene, Crescendo Bioscience, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, and UCB, Speakers bureau: Abbvie, Amgen, BMS, Celgene, Crescendo Bioscience, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer and UCB, G. Schett: None declared, B. Kirkham Grant/research support from: AbbVie, Eli Lilly, Novartis, Roche and UCB, Consultant for: Abbott, Eli Lilly and Novartis, Speakers bureau: Abbott, Janssen, Novartis and Pfizer, V. Strand Consultant for: AbbVie, Amgen, BMS, Celgene, Celltrion, Corrona, Genentech/Roche, GSK, Janssen, Lilly, Merck, Novartis, Pfizer, Regeneron, Sanofi and UCB, N. Williams Consultant for: Novartis through employment at RTI, Employee of: RTI Health Solutions, T. Fox Shareholder of: Novartis, Employee of: Novartis, L. Pricop Shareholder of: Novartis, Employee of: Novartis, S. Jugl Shareholder of: Novartis, Employee of: Novartis, K. Gandhi Shareholder of: Novartis, Employee of: Novartis